Prevalence of Anaemia Among Pregnant Women in Rural and Urban Areas in Zawia City - Asmahan Krayem,; Khadija Alkadaa,; Marwa Almisawi, (AlQalam Journal of Medical and Applied Sciences, 2025)
Anemia is one of the most common blood diseases in the world, which may cause death among mothers, and it is a pathological condition that results from a lack of red blood cells or a decrease in the level of haemoglobin from the normal rate, which leads to the inability of the blood to transport oxygen in the body. Anemia in pregnant women is a major health problem facing various countries of the world, especially developing countries, because of the harmful effects of anemia on the productive, mental, and educational capacity, in addition to the risk of premature birth and having babies who weigh less than normal and suffer from anemia. The main aim of this study was to determine the prevalence of anaemia among pregnant women in both rural and urban areas of Zawiya City, and to correlate it with the type and degree of anaemia. Among pregnant subjects of the age group 19 – 49 years, comprising 50 subjects selected from rural areas and 50 subjects from urban areas of Al-Zawiya in Libya. The haematological parameters, Hb, MCV, RBC, MCH, were investigated by Haematology Analyser - automated blood cell counter. Among the total sample of 100 pregnant women in the 19-49 years age group, the overall prevalence of anemia was observed to be 54%, with 28% in rural area pregnant women and 18% in urban area pregnant women. The results showed that in rural areas, the largest incidence of anemia was (26.1%) in the second trimester, while in urban areas it was (23.9%) in the third trimester. the majority of anaemic cases in rural study cases were (28.3%) in the age category (39-49), while in urban areas the category (19-28) was (23.9%) the most prevalent in rural areas, the degree of anemia severity was moderate anemia (43.5%), and in urban areas, was mild anemia (17.4%). Anemia is still a main health issue in pregnant women in both rural and urban areas. This study, concluded that the prevalence of anemia among pregnant women was high, and the Greater proportion of pregnant women in rural area were suffering from anemia that was moderate type than that urban pregnant woman that was mild type prevalence in rural cases was common in in 2nd trimester however in urban cases was in 3ed trimester The most prevalence anemia types were nutritional deficiency such as iron deficiency, vitamin B 12, and folate.